Karakterisasi Daerah Intron 1 Gen C-C Ligan 7 (CCL7) pada Penderita Asma di Kabupaten Manokwari - Dewi Oktaviami Rahmawati; Achmad Taher; Muhammad Fajar Islam (Jurnal Natural, 2021)
Asthma is a chronic respiratory disease that fluctuates and is one of the most important health problems in the world. Asthma causes obstruction of air flow in the respiratory tract which can make it difficult for sufferers to breathe. Asthma is caused by environmental factors and genetic factors. One of the genetic studies related to asthma explains that there is a gene that plays a role in asthma, namely the C-C Ligand 7 (CCL7) gene. In a previous study, it was found that the intron 1 region of the CCL7 gene was the area with the most polymorphisms. A total of four asthmatics and two non-asthmatics from Manokwari Regency were analyzed for the intron 1 area of ​​the CCL7 gene. The results of this study showed that the intron region 1 of the CCL7 gene consisted of 506 bp. Of the 6 samples studied, 4 samples of asthmatics and 2 samples of non-asthma in Manokwari Regency, 2 SNP polymorphisms were obtained at positions *6 and *214 with nucleotide diversity (π) of 0.00106. This polymorphism forms 3 types of haplotypes, namely AC, AT and TC with a haplotype diversity value of 0.600 ± 0.215. The results of this study can be concluded that the intron region 1 of the CCL7 gene has low genetic diversity with a small number of samples.